Imperative role of electron microscopy in toxicity assessment: A review. Issue 5 (13th December 2021) - Grover, Aseem; Sinha, Reshma; Jyoti, Divya; Faggio, Caterina
Abstract: Electron microscope (EM) was developed in 1931 and since then microscopical examination of both the biological and non‐biological samples has been revolutionized. Modifications in electron microscopy techniques, such as scanning EM and transmission EM, have widened their applicability in the various sectors such as understanding of drug toxicity, development of mechanism, criminal site investigation, and characterization of the nano‐molecule. The present review summarizes its role in important aspects such as toxicity assessment and disease diagnosis in special reference to SARS‐COV2. In the biological system, EM studies have elucidated the impact of toxicants at the ultra‐structural level in various tissue in conformity to physiological alterations. Thus, EM can be concluded as an important tool in toxicity assessment and disease prognosis. Abstract : Electron microscope : An imperative technique in biological research.